Lapindo Embankment Security Monitoring System Based on IoT - Ayuni, Shazana Dhiya; Syahrorini, Syamsudduha; Jamaaluddin, Jamaaluddin (Department of Electronic and Informatic Engineering Education, Faculty of Engineering, UNY, 2021)
Since 2006 Lapindo mudflow caused by natural gas drilling in Sidoarjo. Nowdays the mudflow still can't be stopped, and to prevent it from resident's houses, embankments were built. Eventough the embankments and guardrails has been built but sometimes the mud flowing into resident's houses while its raining or the embankments were subsidence or reep. Severity, the distance between the embankment and the residents' houses is about 500 m. So far, the handling action while embankments ware subsidence is residents report the accidents to related parties, namely PPLS. But the response is too late and take a long time to occur the accident, so the mud has been flow in to resident's houses. because so far it is still completely manual and there is no monitoring system can detect the accident in the embankments. Therefore with monitoring the embankments with vibration and overflow of the lapindo puddle using wirelless sensor network spread over a number of dike-prone points, then its send to smartphone via Blynk. When the accident happend system monitoring aplication will be warning and send message easly via smartphone. So the existence of this monitoring tool can provide a sense of security to the citizens.